The Epithelial to Mesenchymal Transition in Colorectal Cancer Progression: The Emerging Role of Succinate Dehydrogenase Alterations and Succinate Accumulation - Mimmo Turano; Rosario Vicidomini; Francesca Cammarota; Valeria D’Agostino; Francesca Duraturo; Paola Izzo; Marina De Rosa (Biomedicines, 2023)
Colorectal cancer (CRC) stands as the third most significant contributor to cancer-related mortality worldwide. A major underlying reason is that the detection of CRC usually occurs at an advanced metastatic stage, rendering therapies ineffective. In the progression from the in situ neoplasia stage to the advanced metastatic stage, a critical molecular mechanism involved is the epithelial-to-mesenchymal transition (EMT). This intricate transformation consists of a series of molecular changes, ultimately leading the epithelial cell to relinquish its features and acquire mesenchymal and stem-like cell characteristics. The EMT regulation involves several factors, such as transcription factors, cytokines, micro RNAs and long noncoding RNAs. Nevertheless, recent studies have illuminated an emerging link between metabolic alterations and EMT in various types of cancers, including colorectal cancers. In this review, we delved into the pivotal role played by EMT during CRC progression, with a focus on highlighting the relationship between the alterations of the tricarboxylic acid cycle, specifically those involving the succinate dehydrogenase enzyme, and the activation of the EMT program. In fact, emerging evidence supports the idea that elucidating the metabolic modifications that can either induce or inhibit tumor progression could be of immense significance for shaping new therapeutic approaches and preventative measures. We conclude that an extensive effort must be directed towards research for the standardization of drugs that specifically target proteins such as SDH and SUCNR1, but also TRAP1, PDH, ERK1/2, STAT3 and the HIF1-α catabolism.